RELIEF PADA INTERIOR VIHARA AVALOKITESVARA - Farah Salsabila (LPPM Institut Desain dan Bisnis Bali, 2021)
Relief is an expression of feelings and thoughts poured on a flat plane whose flat surface becomes arising and its position is higher than its background. Reliefs have been known since the days of Hindu Buddha with the discovery oftangibleand culturalartifacts. In its development relief is also found in the building of Avalokitesvara Monastery, Serang Banten. This research method uses qualitative methods, where the analysis is more descriptive. Avalokitasvara Monastery building is located in Pamarican Village, Dermayon Village of Serang City, Banten Province. The Avalokitesvara monastery was built as a proof of Sheikh Sheikh Syarif Hidayatullah's love for Princess Ong Tien. The placement of reliefs in the Avalokitesvara Monastery is located on the wall of the main tunnel. Where there are 10 panels placed facing the right and left side walls, each has a different story. The relief also uses visualization of perspective techniques. Visualization on relief describes the situation of the community at the beginning of the initial construction of the monastery until today. The existence of reliefs in the monastery in addition to being an aesthetic element in the interior, but also acts as a medium to ensede the history of the monastery's journey.